2007
DOI: 10.1111/j.1467-8624.2007.01007.x
|View full text |Cite
|
Sign up to set email alerts
|

I Like to Do It, I'm Able, and I Know I Am: Longitudinal Couplings Between Domain‐Specific Achievement, Self‐Concept, and Interest

Abstract: The longitudinal development of the intraindividual coupling between academic achievement, interest, and self-concept of ability (SCA) was analyzed in a sample of approximately 1,000 children between grades 1 and 12 (ages 6-17). Across all calculated indexes, the average level of coupling was positive. Individuals generally felt competent and interested in domains where they achieve well, and were interested in domains where they perceive their personal strengths. The degree of coupling was the highest between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

32
302
5
22

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(361 citation statements)
references
References 76 publications
32
302
5
22
Order By: Relevance
“…They found that the findings of these studies indicated a positive relationship between self-efficacy and performance, which are in line with the findings in other research domains such as math and education in general (Dennissen et al, 2007;Multon et al, 1991;Pajares, 1996).…”
supporting
confidence: 78%
“…They found that the findings of these studies indicated a positive relationship between self-efficacy and performance, which are in line with the findings in other research domains such as math and education in general (Dennissen et al, 2007;Multon et al, 1991;Pajares, 1996).…”
supporting
confidence: 78%
“…academic performance has significant implications for adolescents' selfconcept, as it would be taken as the key criterion for assessing a student in societies emphasizing education (e.g., in China). Many studies suggest that self-concept is closely tied to academic achievement in adolescents (e.g., Denissen, Zarrett, & Eccles, 2007;Kobal & Musek, 2001). However, previous studies have paid attention to how positive and negative feedback regarding adolescents' academic achievement influences their selfconcept but neglected the possibility that cognitive strategies used by adolescents for dealing with this feedback influence their self-concept, as well.…”
mentioning
confidence: 99%
“…Second, it is increasingly clear that cross-sectional relationships between FIs and behavioral traits frequently replicate in within-person studies, or when the associated FIs are directly manipulated (Dweck & Leggett, 1988;Fleeson, Malanos, & Achille, 2002;Higgins, 2000;McCabe & Fleeson, 2012;Metcalfe & Mischel, 1999). Third, behaviors, abilities, expectancies, motives, and associated life experiences appear to generally reinforce and show "corresponsive" causal relationships with one another (Denissen, Zarrett, & Eccles, 2007;Roberts & Wood, 2006). On the basis of these numerous considerations, we believe that our base expectation should be that the correlational relationships identified here generally indicate causal effects of FIs on the behavioral traits they are associated with.…”
Section: Summary Of the Empirical Illustrationsmentioning
confidence: 99%
“…Some of these will include predictable influences of FIs on one another; for instance, if an individual increases in their desire to attain a particular goal, the individual can be expected to increase in their ability to do so, and vice versa (Bandura, 1986;Denissen et al, 2007;Lent, Brown, & Hackett, 1994). The causal effects of the ability, expectancy, and valuation trait classes on one another can be understood through the same overarching functionality assumption that links these three trait classes to behavioral traits (Wood & Denissen, in press).…”
Section: How Are Levels Of Functionality Indicators Shaped?mentioning
confidence: 99%